Short-Chain Fatty Acids and Neurodegeneration in Alzheimer's Disease: A Narrative Review - Komang Trisna Sumadewi; Dewa Ayu Agung Alit Suka Astini; Luh Gde Evayanti; Ida Ayu Laxmi Ananda Dewi Manuaba; Ni Made Gita Kusuma Dewi (CV. Publikasi Indonesia, 2026)
Background: Alzheimer Disease remains the most prevalent cause of dementia worldwide, representing a major and escalating global health challenge. Objective: This study aims to examine the role of short chain fatty acids in the pathogenesis and progression of Alzheimer Disease within the framework of the microbiota gut brain axis. Methods: The research employed a qualitative design with a descriptive approach through a narrative literature study. Data were collected through systematic searches of peer reviewed scientific articles published between 2015 and 2026, focusing on gut microbiota dysbiosis, short chain fatty acids, neuroinflammation, amyloid pathology, and cognitive decline in Alzheimer Disease. Document analysis was conducted using thematic identification, data reduction, conceptual categorization, and inductive interpretation to generate a comprehensive synthesis of the evidence. Results: The findings indicate that Alzheimer Disease is consistently associated with reduced abundance of short chain fatty acid producing bacteria and altered circulating and fecal short chain fatty acid profiles, which are linked to impaired blood brain barrier integrity, microglial activation, increased neuroinflammation, amyloid beta accumulation, and tau pathology. Mechanistic insights demonstrate that short chain fatty acids regulate inflammatory signaling pathways, epigenetic modulation, mitochondrial bioenergetics, and metabolic homeostasis. Conclusion: In conclusion, short chain fatty acids function as key metabolic mediators in Alzheimer Disease and represent promising targets for preventive and therapeutic strategies, contributing to a systems biology perspective and supporting microbiome based precision approaches in cognitive health management.